Aile Konutu Üzerinde Kurulan İpoteğin Eş Rızası Yokluğu Nedeniyle Yolsuz Hale Gelmesinden Kaynaklanan Zarardan Devletin Sorumluluğu - (:unkn) unknown (My University, 2018)
Bu çalışmada aile konutuna ilişkin TMK. M. 194’te yer alan sınırlamadan yola çıkılarak, ailekonutu üzerinde, hak sahibi olmayan eşin rızası olmadan kurulduğu için yolsuz hale gelen ipotektenkaynaklanan zarardan devletin sorumluluğunun bulunup bulunmadığı hususu incelenecektir. Buneticeye ulaşırken de aile konutu, eş rızası, aile konutu şerhi, tapu siciline güven ve ipotek gibi hukukikavramlar da incelenecektir.

In this study, by way of the limit set forth in Turkish Civil Code article 194, the subject of the study is whether the liability of the state for the damages arising from the mortgage which -was established on the family dwelling- become wrongful entry as it was established without the consent of spouse who has not right regarding matrimonial home. While discussing this issue, legal concepts such as family dwelling, consent of spouse, family dwelling endorsement, trust in land registry and mortgage will also be examined.
Liability of The State of Damage Caused By The Invalidity of The Mortgage on The Family Dwelling Due to Lack of Consent Of Spouse
Keywords: İşletme Finans